2020
DOI: 10.3389/fvets.2020.591558
|View full text |Cite
|
Sign up to set email alerts
|

Spermatotoxic Effects of Single-Walled and Multi-Walled Carbon Nanotubes on Male Mice

Abstract: Carbon-based nanomaterials possess a remarkably high potential for biomedical applications due to their physical properties; however, their detrimental effects on reproduction are also concerned. Several reports indicate the toxicity of carbon nanotubes (CNT); nevertheless, their impact on intracellular organelles in the male reproductive organs has not been fully elucidated. Herein, we report on the reprotoxicity of single-walled (SWCNT) and multi-walled carbon nanotubes (MWCN) on several intracellular events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 110 publications
1
18
0
Order By: Relevance
“…The level of toxicity of CNTs is strictly related to applied concentration. Thus, the oral uptake of CNTs in high concentrations (10 and 50 mg/kg) led to reproductive system injury and sperm toxicity in male mice . Here, we confirmed that a high dose of CNTs (10 mg/kg) administrated orally can lead to liver damage.…”
Section: Resultssupporting
confidence: 77%
“…The level of toxicity of CNTs is strictly related to applied concentration. Thus, the oral uptake of CNTs in high concentrations (10 and 50 mg/kg) led to reproductive system injury and sperm toxicity in male mice . Here, we confirmed that a high dose of CNTs (10 mg/kg) administrated orally can lead to liver damage.…”
Section: Resultssupporting
confidence: 77%
“…We used MDA while Zhou et al [ 40 ] used DCFH-DA. MWCNTs trigger oxidative stress damage of testis [ 50 ] and neurons [ 15 ] in mice. MWCNTs increased the oxidative stress marker MDA and decreased the antioxidant markers in the rat kidney [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The eosin-nigrosin staining was used to evaluate spermatozoa viability and abnormality ( 51 , 52 ). Briefly, the extracted caudal epididymal germ cells (100 μL) were incubated in PBS (35°C; pH = 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Spermatozoa smear was stained with eosin-nigrosin (10 μL). Slides were monitored randomly for viability assay, where unstained germ cells were considered live ( 51 , 52 ). The germ cells with ab-axial tail, protoplasmic droplets, double tails, malformed heads, coiled tails, bent tails, and without tail and head were considered abnormal.…”
Section: Methodsmentioning
confidence: 99%